Penggunaan Teori Konseling dalam Layanan Konseling Individu di SMP Kabupaten Gresik - mufidah, elia firda; Lathifah, Maghfirotul (Jurnal Bimbingan dan Konseling Terapan, 2020)
Individual counseling is part of the existing services in guidance and counseling. Individual counseling in its implementation cannot be separated from counseling theory. Counseling theory provides guidance in the course of the counseling process. It is hoped that the use of the counseling theory can become a guide for guidance and counseling teachers so that during the counseling process they do not turn towards the sharing and advising session. This research uses a descriptive qualitative approach. The subject of this research is the Guidance and Counseling Teacher at SMP Gresik Regency as the main informant. The research had the aim of obtaining an overview of the use of counseling theory by Guidance and Counseling teachers at SMP Gresik Regency